Catalysis of electrodes in nanoscales for high performance dye-sensitized solar cell. - Guai, Guan Hong. (2013)
To achieve high power conversion efficiency (PCE) in dye-sensitized solar cell (DSSC) under illumination, favorable catalytic electrochemical reactions need to occur at the photoelectrode (i.e. oxidation) and counter electrode (i.e. reduction) respectively, which in turn are propelled through effective charge transport/transfer in the device. Therefore, this PhD project focuses on the smart engineering of nanomaterials and structural modifications in nanoscales to improve the catalysis of DSSC electrodes for enhanced device performance and economic sustainability while exploring the charge transport/transfer mechanisms to gain fundamental knowledge. In this study, it is demonstrated that specific tailoring of a TiO2 compact layer enhances charge harvesting at the photoelectrode through better interfacial bonding and charge transportation. Furthermore, it is also revealed that only charge transport enhancers with semiconducting nature could result in a synergistic effect of fast electron shuttling across the photoelectrode while suppressing charge recombination for higher device PCE. In addition, the electrochemical activity of a DSSC counter electrode can also be improved by designing and fabricating nanomaterials with desirable charge transfer properties and large effective catalytic surface area, such as graphene-Pt and sulfur-doped nickel oxide.